Chromosome‐level genome assembly of Paralithodes platypus provides insights into evolution and adaptation of king crabs. (22nd October 2020) - Tang, Boping; Wang, Zhongkai; Liu, Qiuning; Wang, Zhengfei; Ren, Yandong; Guo, Huayun; Qi, Tingting; Li, Yuetian; Zhang, Huabin; Jiang, Senhao; Ge, Baoming; Xuan, Fujun; et al.
Abstract: The blue king crab, Paralithodes platypus, which belongs to the family Lithodidae, is a commercially and ecologically important species. However, a high‐quality reference genome for the king crab has not yet been reported. Here, we assembled the first chromosome‐level blue king crab genome, which contains 104 chromosomes and an N50 length of 51.15 Mb. Furthermore, we determined that the large genome size can be attributed to the insertion of long interspersed nuclear elements and long tandem repeats. Genome assembly assessment showed that 96.54% of the assembled transcripts could be aligned to the assembled genome. Phylogenetic analysis showed the blue king crab to have a close relationship with the Eubrachyura crabs, from which it diverged 272.5 million years ago. Population history analyses indicated that the effective population of the blue king crab declined sharply and then gradually increased from the Cretaceous and Neogene periods, respectively. Furthermore, gene families related to developmental pathways, steroid and thyroid hormone synthesis, and inflammatory regulation were expanded in the genome, suggesting that these genes contributed substantially to the environmental adaptation and unique body plan evolution of the blue king crab. The high‐quality reference genome reported here provides a solid molecular basis for further study of the blue king crab's development and environmental adaptation.